In a New Light: Early African American Photography - Sheehan, Tanya (American Studies, 2013)
This review essay reviews: The Camera and the Press: American Visual and Print Culture in the Age of the Daguerreotype, by Marcy J. Dinius; Pictures and Progress: Early Photography and the Making of African American Identity, by Maurice O. Wallace and Shawn Michelle Smith; Embracing Black Experience: Stillness, Critical Memory, and the Black Body, by Harvey Young; Delia’s Tears: Race, Science, and Photography in Nineteenth-Century America, by Molly Rogers and David W. Blight.